Lantbrukares möjlighet till en investering i solceller - Nygren, Richard (SLU/Dept. of Economics, 2009)
When the costs for a company increase it is normal to look for alternatives to lower these costs. One of the expenditure that farmers have is energy costs. The price for the energy may vary because of the free market. To look at the possibilities for a farmer to invest in sun power, to make the company less sensitive for the changes on the electrical market, is interesting. The biggest part of the electricity that is produced in Sweden comes from a few companies on the market. Two types of produced electricity dominate the market. These are electricity made from nuclear power and electricity made from hydroelectrically power. Renewable sources that do not affect the environment are today a minority of all the produced electricity.